2018
DOI: 10.20435/inter.v19i3.1667
|View full text |Cite
|
Sign up to set email alerts
|

Amazônia no Antropoceno: o manejo como relação entre humanos e fauna silvestre

Abstract: Amazônia no Antropoceno: o manejo como relação entre humanos e fauna silvestreAmazon in the Anthropocene: management as a rela onship between humans and wildlife Amazon dans l'anthropocène: la ges on en tant que rela on entre les humains et la faune Resumo: O trabalho foi realizado para discu r a conservação e manejo da fauna silvestre amazônica a par r da relação entre humano e não humano como respostas a defaunação na época do Antropoceno. Na Amazônia, essas prá cas transformam o modo como as populações huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…The different types of management were mentioned as some of the most plausible solutions, as strategies to confront species extinction, mitigate processes and minimize environmental crisis (Mateus et al, 2017) in the elaboration of conservation and preservation measures (Oviedo & Crossa, 2013). Moreover, as a possibility of dealing with climate change (Lawler, 2009), improving the resilience of riparian ecosystems, minimizing impacts (Palmer et al, 2008), and contributing to the recovery of the complex, structured and spatial units -if the interdependent relationship is maintained between the actors and factors, whether they are biotic, physical or socioeconomic (Berkes, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The different types of management were mentioned as some of the most plausible solutions, as strategies to confront species extinction, mitigate processes and minimize environmental crisis (Mateus et al, 2017) in the elaboration of conservation and preservation measures (Oviedo & Crossa, 2013). Moreover, as a possibility of dealing with climate change (Lawler, 2009), improving the resilience of riparian ecosystems, minimizing impacts (Palmer et al, 2008), and contributing to the recovery of the complex, structured and spatial units -if the interdependent relationship is maintained between the actors and factors, whether they are biotic, physical or socioeconomic (Berkes, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Além desses aspectos, somam-se ao contexto das práticas de manejo na região amazônica, questões intersubjetivas da relação entre as sociedades ameríndias e os animais não humanos (DESCOLA, 1998(DESCOLA, , 2012VIVEIROS DE CASTRO, 1996, cujo mundo é permeado de pessoas de outras espécies e demais entidades, que fazem parte da epistemologia indígena. Nesse sentido, Mateus et al (2018) discutem que o manejo como estratégia de conservação de espécies ameaçadas de extinção pode ser benéfico, mas para que isso ocorra, deve-se enfatizar a relação sensível entre humano e não humano e aglutinar os conhecimentos ecológicos, biológicos e etológicos para dar maior eficiência ao manejo.…”
Section: Estruturas E Processos Na Conservação Da Fauna Silvestreunclassified
“…The pirarucu is a species that is native to the Amazon region (MATEUS et al, 2017). It is notable for being large (BARD et al, 1986) and is found in countries such as Peru, Bolivia, Colombia, Ecuador, and Guiana, living in rivers, lakes and other fresh water environments where temperatures range from 24 o to 37 o C. It is not usually found in places with strong currents and/or in waters with sediments (BARD et al, 1986).…”
Section: Introductionmentioning
confidence: 99%